2006
DOI: 10.1177/0040517506062648
|View full text |Cite
|
Sign up to set email alerts
|

Compact Spinning Effect on Cotton Yarn Quality: Interactions with Fiber Characteristics

Abstract: Compact or condensed spinning technology is widely considered as the new benchmark for staple yarn quality. The enhanced structure of compact yarn typically results in a lower hairiness and improved mechanical properties. The present study examines these two key benefits of compact technology when applied to short-to-medium staple cotton. The main focus is on interaction effects involving various raw fiber properties rather than on the overall effects. The results show that, with some combinations of fiber cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 10 publications
0
33
0
1
Order By: Relevance
“…Krifa and Ethridge (2003),Krifa and Ethridge (2006) andStrumiłło et al (2007), came to similar conclusion.…”
mentioning
confidence: 67%
“…Krifa and Ethridge (2003),Krifa and Ethridge (2006) andStrumiłło et al (2007), came to similar conclusion.…”
mentioning
confidence: 67%
“…Nevertheless, the conventional ring‐spun yarn type of sample A is better than the Estex yarn type of other fibre types, i.e. fabric samples D and F, which means that Pima cotton performs better in dyeability than the other fibre types, regardless of yarn type [6,13]. Therefore, it is suggested that, if Pima cotton is selected as the fibre type for manufacturing, Estex spinning technology may not be necessary for improving its dyeing properties as its conventional ring‐spun yarn type has already achieved a better colour depth.…”
Section: Resultsmentioning
confidence: 99%
“…A scanning electron microscopic view shows ( Figure 3) that a more compact yarn structure would be obtained as the yarns get finer [21]. The compact structure also shows less protruding fibers on the outer surface of the yarn, which will lead to less hairiness, increased uniformity and yarn strength [8] [9] [22]- [26].…”
Section: Literature Reviewmentioning
confidence: 99%